The influence of the area of attack on point success in men`s professional beach volleyball - Jimenez Olmedo, J. M.; Penichet-Tomas, A.; del Mar Silvestre Garcia, M.; Chinchilla Mira, J. J.; Perez-Turpin, J. A.; Suarez Llorca, C. (World Congress of Performance Analysis of Sport IX, 2012)
This study was developed during the First International Training Tournament Sixto Jimenez, played in Tenerife (Spain) in 2010. The analysis of video recordings was performed with the software SportCode Pro. Therefore, the aim of this study is to identify areas (picture 1) of the field where win, lose or continue the attacks, determining in this way, what are the areas where higher scores are achieved. Quantitative analysis with a sample of 10 teams played 12 games with a total of 1027 attacks analyzed. The data analysis was performed with SPSS v.18 software, the Mann-Whitney test showed significant differences in certain areas. Of the attacks wins, 27% (p = .05) are achieved by leaving the ball out of bounds after being touched by an opposing team member, as well as a Zone 1 and Zone 2 21% to 11% . As for the continuation of points, significant differences were found both in zone 1, 2, the most consistent area 5 (p = 0.05). The points lost due to the blocking action of the opposing team as well as attacks where the ball strikes the net or falls outside the field (p = 0.05).